2013
DOI: 10.3892/ijo.2013.2007
|View full text |Cite
|
Sign up to set email alerts
|

CD59 is overexpressed in human lung cancer and regulates apoptosis of human lung cancer cells

Abstract: CD59, belonging to membrane complement regulatory proteins (mCRPs), inhibits the cytolytic activity of complement and is overexpressed in many types of solid cancers. The aim of the present study was to detect the expression of CD59 in non-small cell lung cancer (NSCLC) and to investigate the relationship between decreased CD59 expression and tumorigenesis of NSCLC by transfecting recombinant retrovirus encoding shRNA targeting human CD59 into the human NSCLC cell line NCI-H157. CD59 expression in NSCLC was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…In addition, CD59 overexpression protects MCF-7 breast cancer cells from complement-mediated cytolysis and promotes MCF-7 cell proliferation by inhibiting BCL-2 expression; conversely, CD59 knockdown upregulates Fas and caspase-3 to induce apoptosis (20). Besides, CD59 silencing in NSCLC cancer cells can enhance complement-mediated cell apoptosis and inhibit the growth of NSCLC (16), which shows accordance with our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, CD59 overexpression protects MCF-7 breast cancer cells from complement-mediated cytolysis and promotes MCF-7 cell proliferation by inhibiting BCL-2 expression; conversely, CD59 knockdown upregulates Fas and caspase-3 to induce apoptosis (20). Besides, CD59 silencing in NSCLC cancer cells can enhance complement-mediated cell apoptosis and inhibit the growth of NSCLC (16), which shows accordance with our study.…”
Section: Discussionsupporting
confidence: 79%
“…To escape complement attack, tumor cells express high levels of membrane complement regulatory proteins (mCRPs) (13 3,4,6 , RONGCHENG LUO 5 and ZHIMING SHAO complement activation, is considered to be the most effective mCRP at protecting cancer cells by inhibiting MAC formation (14). CD59 is widely expressed, and its expression levels are higher in almost all cancer cells than in adjacent normal cells (14)(15)(16), which facilitates tumor cell escape from complement attack (17,18). Although previous reports have described CD59 as a prognostic biomarker in breast cancer (19)(20)(21) playing important roles in immunotherapy of human malignancies (22), the role of CD59 in breast cancer growth and prognosis has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although markers for clathrin- and caveolae-independent endocytotic pathways are less well characterized, glycophosphatidylinositol-anchored proteins (GPI-AP) are reportedly internalized by these routes (15, 17, 18). For our studies, we chose complement lysis restricting factor/CD59 (31), a GPI-AP that is involved in cellular processes critical to lung cancer cell survival and internalized via CIE (32, 33). Recent studies have identified the transmembrane glycoprotein, CD44, which is a hyaluronic acid receptor, as a cargo molecule specifically internalized by CLICs and recycled via GPI-enriched endocytic compartments (GEEC; refs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, four genes out of the nine with UTR-APA have been found to be either overexpressed in cancer: PSMD8 (27), CD59 (29), and SRSF5 (32) or is suggested to be overexpressed: ANKH (30). The UTR-APA in these genes produces mRNA isoforms that lack one or more target sites for miRNAs present in SI-NETs.…”
Section: Discussionmentioning
confidence: 99%